2000
DOI: 10.1128/aem.66.3.920-924.2000
|View full text |Cite
|
Sign up to set email alerts
|

Copper Induction of Laccase Isoenzymes in the Ligninolytic Fungus Pleurotus ostreatus

Abstract: Pleurotus ostreatus is a white rot basidiomycete that produces several extracellular laccase isoenzymes, including phenol oxidase A1b (POXA1b), POXA2, and POXC. POXC was the most abundant isoenzyme produced under all of the growth conditions examined in this study. Copper was the most efficient inducer of laccase activity among the putative inducers tested. The amounts of all of the previously described laccase isoenzymes increased substantially in copper-supplemented cultures. Under these conditions expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
310
6
23

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(362 citation statements)
references
References 25 publications
23
310
6
23
Order By: Relevance
“…1B). Copper is a laccase cofactor which presents four cupric ions each associated with one single polypeptide chain (23) but it also has been proved that this element may play an important role in laccase genes regulation at transcription level as showed in Trametes versicolor (7) Phanerochaete chrysosporium (9), Pleurotus ostreatus (18) and Coriolopsis rigida (20). The 250 µM Cu provided the highest laccase activity in LN cultures, which is in accordance to the findings for other fungi, like T. versicolor (400 µM) (7), P. ostreatus (1.0 mM) (3) and V. volvacea (200 µM) (6).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Copper is a laccase cofactor which presents four cupric ions each associated with one single polypeptide chain (23) but it also has been proved that this element may play an important role in laccase genes regulation at transcription level as showed in Trametes versicolor (7) Phanerochaete chrysosporium (9), Pleurotus ostreatus (18) and Coriolopsis rigida (20). The 250 µM Cu provided the highest laccase activity in LN cultures, which is in accordance to the findings for other fungi, like T. versicolor (400 µM) (7), P. ostreatus (1.0 mM) (3) and V. volvacea (200 µM) (6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have stressed the importance of copper in the regulation of laccase at the transcriptional level Soden & Dobson, 2001;Palmieri et al, 2000;Galhaup et al, 2002). We previously demonstrated that under low-copper conditions, lcs-1 is not efficiently transcribed in C. subvermispora .…”
Section: Discussionmentioning
confidence: 99%
“…Laccase isoenzyme multiplicity is a phenomenon observed in several fungi, and in the case of Pleurotus sajor-caju (Soden & Dobson, 2001), the basidiomycete CECT 20197 (Mansur et al, 1997), Pleurotus ostreatus (Palmieri et al, 2000), Trametes villosa , Agaricus bisporus (Perry et al, 1993) and Rhizoctonia solani (Wahleithmer et al, 1995), families of structurally related genes have been described. In the case of C. subvermispora, over four isoforms are observed, with different substrate specificity, but only one gene, lcs-1, has been identified Salas et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Laccase is a copper-dependent enzyme, and the enzyme immobilized in copper alginate is likely to retain more activity than laccase immobilized using other methods. Laccase of Pleurotus ostreatus and Ganoderma sp were successfully entrapped in copper alginate beads and decolorized some synthetic dyes efficiently (Palmieri et al 2000;Teerapatsakul et al 2008). The biotreatment of industrial effluents that contain heavy metals, detergents, copper chelating agents and phenolic compounds arises a great concern to industries as these compounds are either toxic to microbes or they act as non-competitive inhibitors or as denaturing agents for several enzymes.…”
Section: Introductionmentioning
confidence: 99%